The practice of gender and protection mainstreaming in health response in humanitarian crisis - A case study from the refugee camps in Cox's Bazar, Bangladesh. - Charls Erik Halder; Md Abeed Hasan (PLoS ONE)
Background The health system is required to be safe, equitable, and accessible to all ages, gender, and vulnerable groups, including older persons and persons with disability, and address their specific needs and concerns. However, limited evidence is available on the effectiveness and practicality of gender and protection mainstreaming interventions in health response in humanitarian crises. Objective The overall objective of the research was to explore practices, gaps, and challenges and generate recommendations regarding gender and protection mainstreaming in health response to the Rohingya refugee crisis in Cox's Bazar, Bangladesh. Methodology The research employed a qualitative case study design to explore the practice of gender and protection mainstreaming in health response in Cox's Bazar. Data collection methods include an extensive literature review and in-depth interviews with professionals. The professionals interviewed from the area of health and protection, specifically gender, child protection, emergency health intervention, and primary health activities. Data were analyzed using thematic analysis related to gender and protection mainstreaming. Limitations were assessed as to researcher bias because the researcher did all the coding; however, an open recording process, inter-literature cross-potentiation, and ethical considerations of research helped add to the reliability of the research. Exclusion criteria were defined to ensure data consistency, removing insufficiently detailed responses not pertinent to the research objectives. Result The study found a range of good practices on gender and protection mainstreaming in health response, e.g., placement of a gender action plan, monitoring system for gender and disability inclusion, emergency preparedness and response system, availability of sex-segregated toilets and waiting spaces, availability of gender-based violence service and engagement of female community health workers. The study also revealed some best practices which have the potential to scale up, e,g. psychosocial spaces at health facilities for children, palliative care for terminally ill patients, integrated medical and protection services, and facilitation of community health facility support groups. Critical gaps were found in the areas of women's leadership, coordination, capacity building, targeted interventions for vulnerable groups, infrastructural adaptation and consultation with the community on their concerns. Conclusion We urge policymakers, sector coordinators, health program management, healthcare workers, and global stakeholders to address the gaps and challenges, learn and scale up the best practices, and take action to implement the study's recommendations to maximise gender and protection mainstreaming in health response.